Role of TREK-1 in Health and Disease, Focus on the Central Nervous System - Djillani, Alaeddine; Mazella, Jean; Heurteaux, Catherine; Borsotto, Marc (Frontiers in Pharmacology, 2019)
TREK-1 is the most studied background K2P channel. Its main role is to control cell excitability and maintain the membrane potential below the threshold of depolarization. TREK-1 is multi-regulated by a variety of physical and chemical stimuli which makes it a very promising and challenging target in the treatment of several pathologies. It is mainly expressed in the brain but also in heart, smooth muscle cells, endocrine pancreas and prostate. In the nervous system, TREK-1 is involved in many physiological and pathological processes such as depression, neuroprotection, pain and anesthesia. These properties explain why many laboratories and pharmaceutical companies have been focusing their research on screening and developing highly efficient modulators of TREK-1 channels. In this review, we summarize the different roles of TREK-1 that have been investigated so far in attempt to characterize pharmacological tools and new molecules to modulate cellular functions controlled by TREK-1.